Penguatan Toleransi dan Identitas Sosial Melalui Halalbihalal Lintas Agama Pada Masyarakat Kampung Gendingan, Yogyakarta - Aulia Rahmawati; Joko Tri Haryanto (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2020)
Religious plurality has been a challenge in building tolerance and religious harmony in Indonesia. But people has a way to maintain social integration, among which is the tradition of halal bihalal on Eid Mubarak momentum. In Java, it can strengthen good relations between individuals and even among different religions, as shown by Muslims and Christians in Gendingan, Yogyakarta. This study aimed at revealing how the halal bihalal phenomonon across religions in Gendingan could serve as a driving force for religious tolerance and social identity of the people. The study used a qualitative approach in which data were collected through interviews, observation, and documentation. The findings of this study indicated that interfaith halal bihalal as the public consensus in Gendingan, Yogyakarta is constructed in promoting tolerance values between religious believers and breaking down social identity barriers that are restricted  by religious identity. In social life where there is a plurality of religions, interfaith halal bihalal is capable of encouraging greater acceptance of social identity than religious identity, namely a shared social identity as a member of Gendingan village. A strong social identity as citizens has beaten the different of religious identity in building an attitude of religious tolerance and harmony.